Kompensasi, Iklim Organisasi, Dan Kepuasan Kerja Terhadap Kinerja Karyawan PT. PEB - Sri Langgeng Ratnasari; Gandhi Sutjahjo (Jurnal MEBIS (Manajemen dan Bisnis), 2017)
This reserach aims to effect of compensation, organizational climate, job satisfaction on employee performance of PT. PEB. This research uses 85 employees of PT. PEB as the study sample. The data analyzed using “Path Analysis” path by using statistical software SPSS 16.0. The research results are: Compensation direct and significant effect on job satisfaction with path coefficient of 0.387, and significant at the 0.000 Sig probability, ≤ α = 0.05, Organizational climate has direct and significant effect on job satisfaction with the value of the path coefficient amounted to 0.512, and significant at the 0.000 probability Sig, ≤ α = 0.05, job satisfaction is directly and significantly impact on performance with the path coefficient of 0.648, and significant at the 0.000 Sig probability, ≤ α = 0.05, the compensation effect indirectly to job performance through job satisfaction and the indirect effect coefficient> direct influence (p31 x p43> p41) ie 0.329> 0.078, organizational climate indirectly influence on employee performance through job satisfaction and indirectly influence coefficient> influence directly (p32 x p43> p42) ie 0.332> 0.179.